HUBUNGAN ANTARA PERSEPSI MASYARAKAT TENTANG MENGURAS, MENGUBUR, DAN MENUTUP (3M) DENGAN PENCEGAHAN DEMAM BERDARAH DENGUE (DBD) DI DESA SELOKERTO KECAMATAN SEMPOR KABUPATEN KEBUMEN - Sarwono -; marsito -; Agustina Tri Hastuti (LPPM UNIVERSITAS MUHAMMADIYAH GOMBONG, 2009)
Dengue Hemmorrhagic Fever (DHF) is an important community health problem and it represents as an epidemic disease. Selokerto village is one of dengue hemmorrhagic fever endemic areas. In this village dengue cases are always increasing. In 2007, there were is 16 patients infected by dengue hemmorrhagic fever and it increased become 18 patients in 2008. Dengue Hemmorrhagic Fever prevention can be done by Draining (clean the water containers such as bathroom and others which become the place for saving water), Burrying (burry all containers that are not used anymore such as cans, bottles, etc), and Covering (cover/close the water supply containers) program. The objective of the research was to find out correlation between community perception about draining, burrying, and covering with Dengue Hemmorrhagic Fever (DHF) Prevention in Selokerto Village, Sempor, Kebumen Regency. The design used in the research was descriptive correlation with cross sectional approach. The data were analized by using Kendall Tau test to find out wether there was correlation between the variables. Research finding showed that respondents' perception of Draining, Burrying, and Covering program: 76 respondents (83%) had good perception, 13 respondents (14%) had good enough perception, and 3 respondents (3%) had bad perception about the program. Meanwhile the result of the experiment also showed the respondents' prevention behaviour of Dengue Hemmorrhagic Fever: 57 respondents (62%) had good prevention behaviour, 26 respondents (28%) had good enough prevention behaviour, and 9 respondents (10%) had bad prevention behaviour. Conclusion: Research finding showed there was significant correlation between community perception about draining, burrying, and covering with Dengue Hemmorrhagic Fever (DHF) Prevention in Selokerto Village, Sempor, Kebumen Regency. Keywords: Community Perception, Draining, Burrying, and Covering, Dengue Hemmorrhagic Fever (DHF) prevention